Effect of vitamin D receptor activators on cardiovascular events in patients on hemodialysis—A post hoc analysis of the LANDMARK study. Issue 3 (7th December 2022) - Yoshida, Kiryu; Mizukami, Takuya; Fukagawa, Masafumi; Akizawa, Tadao; Morohoshi, Hokuto; Sambe, Takehiko; Takeshima, Akiko; Ito, Hidetoshi; Ogata, Hiroaki; Uchida, Naoki
Abstract: Introduction: The clinical benefit of vitamin D receptor activators (VDRA) in patients with well‐controlled secondary hyperparathyroidism undergoing dialysis remains unclear. Methods: This post hoc analysis of the LANDMARK study investigates if VDRA use is associated with cardiovascular benefits. Data of 2135 patients undergoing hemodialysis who were at risk for vascular calcification were analyzed using a Cox proportional hazards model with propensity‐score matching. Results: The hazard ratio (HR) for VDRA use was 0.99 (95% confidence interval [CI]: 0.67–1.46; p = 0.945) for cardiovascular events and 0.89 (95% CI: 0.62–1.28; p = 0.541) for all‐cause mortality at baseline. Among patients who always used VDRA, the HR was 1.12 (95% CI: 0.67–1.89; p = 0.666) for cardiovascular events and 1.11 (95% CI: 0.67–1.85; p = 0.688) for all‐cause mortality compared to those who never used VDRA. Conclusion: The use of VDRA does not reduce the risks of cardiovascular events or all‐cause mortality in patients on dialysis with well‐controlled secondary hyperparathyroidism.